Implementing Total Productive Maintenance in Yemeni Company for Industry and Commerce (YCIC): Case Study - Badiea, A. M.; Wael, B. A.; Adel, A. A. (European Journal of Applied Sciences, 2023)
Purpose: The purpose of this research is to design fundamental base for continuous improvement in maintenance that serves improving machine’s reliability and raises the productivity, to fix strong products in the market with perfect quality and competitive price. Zero breakdowns, zero defects and zero accidents are the target to possibly improve productivity, save costs by reducing wastes and equipment longevity. Making the workplace is healthy organizational environment and better performance, increases the work team spirit by appropriate follow instruction of the implementation and mutual respect and understanding between managers and employees. Design / Methodology / Approach: The data were collected using questionnaire, company’s documentation, interview and observations for 6 months at the lines of the company. The assessment is based on the overall equipment effectiveness (OEE), productivity and profitability approach. Cause-Effect diagram and Pareto chart techniques were used for identifying the problems in the production lines. The 8 pillars and others worksheets of TPM are used for 6 months period. Finally, OEE and its indexes were used as measuring of success the TPM implementation. Findings - The suggested scheme was effective in increasing the overall equipment effectiveness from 48 % to 85 % over a 6 months period. The parameters of OEE were a direct orientation of improvements in equipment availability, performance and product quality by highly recommendation on the pillars of TPM. This work may have exploits on the consistency of TPM nature to improve maintenance scheme for a generic system. The tools and worksheets presented can be helpful to managers and operators. Originality / value: Total productive maintenance (TPM) is one of the numerous diagnostic/prognostic maintenance strategies have been employed in this study. This research has implemented an integrated OEE and its parameters/managers and normal labors in order to clarify the cause / effect to make action for the critical/chronic lines to remedy the low production. This is the first time that the TPM in this company has been placed and its impact is gained after that specific and short period.